¿Qué es ser campesino?: una definición del campesinado desde la Antropología - González Arpide, José Luis; Fernández Álvarez, Oscar (Estudios humanísticos. Geografía, historia y arte, 1992)
The authors of this article, of a theoretical nature, within the field of the peasant studies, take an anthropological approach to try and define peasantry. Thus, it first considers the origen and theoretical development of the generic concept of the peasantry through which the tradition theoretical framework of Peasant Studies hs been formed, so as later consider other aspects. As a concluding remark, they see the analysis of the peasant groups and the relationships with the social struture as the path to be followed by the theoretical debate on peasantry. The authors pay a particular attention to the critical study of the concept.